Effect of mechanical cycling on the push-out bond strength of fiber posts adhesively bonded to human root dentin - Valandro, L. F.; Baldissara, P.; Galhano, G. A.; Melo, R. M.; Mallmann, A.; Scotti, R.; Bottino, M. A. (Operative Dentistry Inc, 2007)
This study evaluated the effect of mechanical cycling on the bond strength of fiber posts bonded to root dentin. The hypotheses examined were that bond strength is not changed after fatigue testing and bond strength does not present vast variations according to the type of fiber post. Sixty crownless, single-rooted human teeth were endodontically treated, with the space prepared at 12 mm. Thirty specimens received a quartz fiber post (Q-FRC (DT Light-Post), and the remaining 30 specimens received a glass fiber post (G-FRC) (FRC Postec Plus). All the posts were resin luted (All Bond+Duolink), and each specimen was embedded in a cylinder with epoxy resin. The specimens were divided into six groups: G1-Q-FRC+no cycling, G2- Q-FRC+20,000 cycles (load: 50N, angle of 45 degrees; frequency: 8Hz); G3- Q-FRC+2,000,000 cycles; G4- G-FRC+no cycling; G5- G-FRC+20,000 cycles; G6- GFRC+2,000,000 cycles. The specimens were cut perpendicular to their long axis, forming 2-mm thick disc-samples, which were submitted to the push-out test. ANOVA (alpha=.05) revealed that: (a) QFRC (7.1 +/- 2.2MPa) and G-FRC (6.9 +/- 2.1MPa) were statistically similar (p=0.665); (b) the no cycling groups (7.0 +/- 2.4MPa), 20,000 cycles groups (7.0 +/- 2.1MPa) and 2,000,000 cycles groups (7.0 +/- 2.0MPa) were statistically similar (p=0.996). It concluded that mechanical cycling did not affect the bond strength of two fiber posts bonded to dentin.